Academic and non-academic predictors of common mental health difficulties among university students during the COVID-19 pandemic - Worsley, Joanne; Dryburgh, Amy; McIntyre, Jason C.; Corcoran, Rhiannon (Frontiers in Public Health, 2024)
Introduction Public concern for the mental health of university students has been rising over recent years. Newly arising stressors associated with the COVID-19 pandemic could contribute to further mental health burden for students. This study aimed to understand the mental health status of university students at an early stage in the pandemic and to identify academic, non-academic, and COVID-19-related predictors of common mental health difficulties at this time. Methods This study examined how academic and non-academic predictors relate to common mental health difficulties using a cross-sectional sample of university students (n = 3817). Results There were high levels of depression and anxiety during the pandemic, with more than 50% experiencing levels above the clinical cut offs. Academic stress, social isolation, intolerance of uncertainty, and more negative attitudes towards remote teaching and learning predicted higher levels of depression and anxiety. University identification predicted lower levels of depression whereas receiving a diagnosis of COVID-19 was associated with higher levels of depression. Discussion This study identified COVID-19-related factors that uniquely contributed to students’ distress during the pandemic, over and above social connectivity variables. As COVID-19 factors, such as the uncertainty surrounding the pandemic, may have driven an increase in distress levels among students, these findings provide insights that could help universities and policymakers develop targeted interventions to support the mental health and well-being of university students during future crises.